Pharmacological Effects of Polyphenol Phytochemicals on the JAK-STAT Signaling Pathway - Yin, Qianqian; Wang, Longyun; Yu, Haiyang; Chen, Daquan; Zhu, Wenwei; Sun, Changgang (Frontiers in Pharmacology, 2021)
The JAK-STAT signaling pathway is a common pathway of many cytokine signal transductions, closely related to cell proliferation, apoptosis, differentiation, and inflammatory response. It is essential for inhibiting the inflammatory response, initiating innate immunity, and coordinating adaptive immune mechanisms. Owing to the nature of this pathway and its potential cross-epitopes with multiple alternative pathways, the long-term efficacy of monotherapy-based adaptive targeting therapy is limited, and the majority of drugs targeting STATs are still in the preclinical phase. Meanwhile, curcumin, quercetin, and several kinds of plant polyphenol chemicals play roles in multiple sites of the JAK-STAT pathway to suppress abnormal activation. Polyphenol compounds have shown remarkable effects by acting on the JAK-STAT pathway in anti-inflammatory, antitumor, and cardiovascular disease control. This review summarized the pharmacological effects of more than 20 kinds of phytochemicals on JAK-STAT signaling pathway according to the chemical structure of polyphenolic phytochemicals.